2010
DOI: 10.2139/ssrn.1567832
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Programs and Labor Supply in Developing Countries - Experimental Evidence from Latin America

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 64 publications
(26 reference statements)
5
43
0
11
Order By: Relevance
“…Studies of Bolsa Familia in Brazil (Ribas and Soares, 2111; Foguel and Paes de Barrios, 2010; Teixeira, 2010), PROGRESA in Mexico (Parker and Skoufias, 2000; Skoufias and di Maro, 2008; Alzua et al, 2010), the Red de Proteccion Social in Nicaragua (Maluccio and Flores, 2005; Maluccio, 2010; Alzua et al, 2010), the BDH programme in Ecuador (Edmonds and Schady, 2008) and PRAF in Honduras (Alzua et al, 2010; Galiani and McEwan, 2012), using a variety of approaches, have not found significant impact on participation in wage employment by adults, female or male, nor reallocation between agricultural and non agricultural sectors. There is some evidence, however, that CCTs have modestly reduced time spent working, for males in Nicaragua (Maluccio and Flores, 2005) and females in Brazil (Teixeira, 2010), and substitution between wage and domestic home work in Brazil (Ribas and Soares, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Bolsa Familia in Brazil (Ribas and Soares, 2111; Foguel and Paes de Barrios, 2010; Teixeira, 2010), PROGRESA in Mexico (Parker and Skoufias, 2000; Skoufias and di Maro, 2008; Alzua et al, 2010), the Red de Proteccion Social in Nicaragua (Maluccio and Flores, 2005; Maluccio, 2010; Alzua et al, 2010), the BDH programme in Ecuador (Edmonds and Schady, 2008) and PRAF in Honduras (Alzua et al, 2010; Galiani and McEwan, 2012), using a variety of approaches, have not found significant impact on participation in wage employment by adults, female or male, nor reallocation between agricultural and non agricultural sectors. There is some evidence, however, that CCTs have modestly reduced time spent working, for males in Nicaragua (Maluccio and Flores, 2005) and females in Brazil (Teixeira, 2010), and substitution between wage and domestic home work in Brazil (Ribas and Soares, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…PROGRESA leads to an increase only in the intensive margin of women labour supply (Alzúa et al, ). This result is consistent with the idea that beneficiary women of CCTs have more time available, because children spend more time at school.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alzúa et al . () is the only study that looks into the effects of (conditional) CTs on labour supply in a cross‐country context using data from three major welfare programmes in South America. By using a binary treatment approach they find statistically insignificant effects.…”
Section: Literature Reviewmentioning
confidence: 99%